2018
DOI: 10.1007/s00784-018-2448-4
|View full text |Cite
|
Sign up to set email alerts
|

Did malpractice claims for failed dental implants decrease after introduction of CBCT in Finland?

Abstract: It is possible that the use of CBCT may result in fewer compensable malpractice claims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
1
1
Order By: Relevance
“…The incidence of dental implant‐related nerve injury out of the total dental implants claims in our study is lower than in some other studies 3,14,15 . The studies reported altered sensation in the mandible following implant placement to be 37%, 29.8%, and 26%, respectively.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The incidence of dental implant‐related nerve injury out of the total dental implants claims in our study is lower than in some other studies 3,14,15 . The studies reported altered sensation in the mandible following implant placement to be 37%, 29.8%, and 26%, respectively.…”
Section: Discussioncontrasting
confidence: 69%
“…At that time point, 76% of the neurosensory deficiencies occurred when the surgeries were planned and performed based on panoramic or periapical radiographs only (without CT scans), whereas neurosensory damage occurred less frequent when surgeries were planned based on CT 16 . A recent study from Finland concluded a fall in the rate of compensable malpractice cases concerning implant failure simultaneously with the use of CBCT radiographs 15 . In a later study, Givol and colleagues reported that long‐term neurosensory changes occurred in 13% of patients 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio de las demandas realizadas por malpraxis en odontología tiene como principal finalidad el establecer sus causas más frecuentes durante el tra-la más riesgosa y proclive a demandas (88,56 %). Esto puede verse influenciado por factores como son la falta de experiencia del operador o el carácter invasivo que caracteriza a dicha etapa, lo que ya ha sido sugerido en la literatura (Marinescu Gava et al, 2018;Perea-Pérez et al, 2011;Pinchi et al, 2014). Los errores asociados a esta fase refieren al compromiso de estructuras circundantes (mayormente lesiones en nervios alveolar inferior y lingual) o errores en la posición o angulación del implante, todos ya descritos como eventos adversos quirúrgicos habituales (Camargo & Van Sickels, 2015;Misch & Wang;Resnik).…”
Section: Discussionunclassified
“…A radical turnaround in clinical procedures and in the way of technical preparation of implantation using CAD/CAM methods is worked. They include the authors' own methods [3,[206][207][208]210,212,223,244,245] regarding data acquisition by means of cone-beam computed tomography (CBCT) in planning and performing implant prosthetic treatment and also in endodontics and orthodontics [408][409][410][411][412][413][414][415][416][417][418][419][420][421][422][423][424][425][426][427].…”
Section: General Characteristics Of the Dentistry 40 Stage Of Designmentioning
confidence: 99%